Players', head coaches and medical personnel knowledge, understandings and perceptions of injury and injury prevention in elite-level women`s football in Ireland - Horan, D.; Kelly, S.; Hägglund, M.; Blake, C.; Roe, M.; Delahunt, E. (Sports Medicine - Open, 2023)
Background: To manage injuries effectively, players, head coaches and medical personnel need to have excellent knowledge, attitudes and behaviours in relation to the identification of risk factors for injury, the implementation of injury prevention initiatives, and the implementation of effective injury management strategies. Understanding the injury context whereby specific personal, environmental and societal factors can influence the implementation of injury prevention initiatives and injury management strategies is critical for player welfare. To date, no qualitative research investigating the context of injury has been undertaken in elite-level women`s football. The aim of our study was to explore the knowledge, attitudes and behaviours of players, head coaches and medical personnel in the Irish Women`s National League (WNL) to injury prevention and injury management. Methods: We used qualitative research methods to explore the knowledge, attitudes and behaviours of players, head coaches and medical personnel in the Irish WNL to injury prevention and injury management. Semi-structured interviews were undertaken with 17 players, 8 medical personnel and 7 head coaches in the Irish WNL. This study is located within an interpretivist, constructivist research paradigm and interviews were analysed using thematic analysis. Results: The participants had incomplete knowledge of common injuries in elite-level football, and many held beliefs about risk factors for injury, such as menstrual cycle stage, which lacked evidence to support them. Jumping and landing exercises were commonly used to reduce injury but evidence-based injury prevention exercises and programmes such as the Nordic curl, Copenhagen adduction and the FIFA 11 + were rarely mentioned. Overall, there was dissatisfaction amongst players with the medical and strength and conditioning (S & C) support with resultant inadequate communication between players, head coaches and medical personnel. Conclusion: Poor quality and availability of medical and S & C support was considered to be a major obstacle in the effective implementation of injury risk reduction strategies and successful return-to-sport (RTS) practices. More original research is required in elite-level women`s football exploring injury risk factors, injury prevention initiatives and contextual RTS strategies so that players, head coaches and medical personnel can use evidence that is both up-to-date and specific to their environment.